Pengembangan Keterampilan Literasi Membaca melalui Pendekatan Kontekstual pada Siswa Kelas III Sekolah Dasar - Ni Komang Evi Yuliantari; I Nyoman Laba Jayanta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low reading literacy skills of elementary school students, particularly in lower grades, which indicate that reading instruction has not been implemented effectively and meaningfully. Reading instruction tends to be mechanical and lacks connections between texts and students’ real-life contexts, while classroom action research examining the application of a contextual approach in third-grade elementary students remains limited. Therefore, this study aims to improve the reading literacy skills of third-grade elementary school students through the implementation of a contextual approach. The study employed a classroom action research design conducted in two cycles involving 20 students. Data were collected through reading literacy tests and observations of students’ learning activities. The data were analyzed using descriptive quantitative techniques by comparing the mean scores and the percentage of learning mastery in each cycle. The results indicate that the continuous implementation of a contextual approach gradually improves students’ reading literacy skills. These findings suggest that the contextual approach creates more meaningful reading instruction oriented toward students’ real-life experiences and is effective in enhancing elementary students’ reading comprehension.